2012
DOI: 10.5483/bmbrep.2012.45.12.138
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM1 influences the proliferation rate of mouse induced pluripotent stem cells

Abstract: Gangliosides play important roles in the control of several biological processes, including proliferation and transmembrane signaling. In this study, we demonstrate the effect of ganglioside GM1 on the proliferation of mouse induced pluripotent stem cells (miPSCs). The proliferation rate of miPSCs was lower than in mouse embryonic stem cells (mESCs). Fluorescence activated cell sorting analysis showed that the percentage of cells in the G2/M phase in miPSCs was lower than that in mESCs. GM1 was expressed in mE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Ganglioside (GD3 d18:1/24:1 m/z 1592.881) was not observed in the differentiated stem cells, but is seen in the control cells. Gangliosides are generally responsible for proliferation and transmembrane signaling [61]. They reside in the lipid raft of the membrane [62] (Figure 7f) and are found to be lower with adipogenesis [63][64][65], which is consistent with our observation.…”
Section: Resultssupporting
confidence: 91%
“…Ganglioside (GD3 d18:1/24:1 m/z 1592.881) was not observed in the differentiated stem cells, but is seen in the control cells. Gangliosides are generally responsible for proliferation and transmembrane signaling [61]. They reside in the lipid raft of the membrane [62] (Figure 7f) and are found to be lower with adipogenesis [63][64][65], which is consistent with our observation.…”
Section: Resultssupporting
confidence: 91%
“…2). Other investigators also reported that exogenously added gangliosides exhibited stimulatory effects on cellular proliferation of induced pluripotent stem [47] and vascular smooth muscle cells [48]. We have reported NSCs express GD3 as a predominant ganglioside [26,49, 50] and it is co-localized with EGFR to regulate cellular proliferation induced by EGF (unpublished data).…”
Section: Discussionmentioning
confidence: 60%
“…OG2 mouse embryonic fibroblast (MEF) and mESCs produce GM3, GM1, and GD1a, but GM1 is not found in OG2 MEF-derived iPSCs (Fig. 3B) (39). Analysis of the cell proliferation rate in OG2 mESCs and iPSCs revealed that iPSCs have a lower proliferation than that of mESCs.…”
Section: Expression Patterns Of Gangliosides In Mouse Pluripotent Stementioning
confidence: 96%
“…In E14 and Oct-4 promoter-EGFP (OG2) mESCs, small amounts of a-series gangliosides, GM3, GM1 and GD1a, were detected by high-performance thin-layer chromatography and immunocytochemistry analysis (38,39). Furthermore, in TC-1 mESCs, only glucosylceramide and lactosylceramide were present (40); however, J1 mESCs contained GM3, GM1, and GD3 ( Fig.…”
Section: Expression Patterns Of Gangliosides In Mouse Pluripotent Stementioning
confidence: 99%
See 1 more Smart Citation